KERJASAMA DAN BAGI HASIL ANTARA PEMILIK MODAL DENGAN PETANI KERAMBA IKAN NILA DI SUNGAI KAPUAS KOTA PONTIANAK - Bahtiar, Eko (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2020)
The main problem faced by cage farmers in running their business is that some of them have enough capital to build a productive business, but they do not have the skills to do it. Some have no capital but have the skills to work as cage farmers. On this basis, they then collaborated. The method used in this research is a qualitative method. The study was conducted in the Kapuas River, Tambelan Sampit Village, East Pontianak District, Pontianak City. The location selection was done purposively with the consideration that the area is a large area with tilapia fish farmers. The results showed that the cooperation carried out by capital owners with cage farmers in Tambelan Sampit village, the equipment used for the business came from owners of capital, while cage farmers as workers. In the collaboration, there is an unwritten agreement but it is well known in general that cage farmers do not share the risk if there is a loss, cage farmers also do not bear the costs of repairs if there is damage to the equipment used during the business. The amount of profit-sharing is determined based on mutual agreement, namely, profit divided by a 50% margin for 50% cage farmers for capital owners. Actions taken if one of the parties feels aggrieved include deciding the working relationship that can be carried out by the capital owner to the cage farmers in Tambelan Sampit already done based on or in accordance with the Islamic concept. Conformity is meant especially when compared with the principles of Muamalah taught by Islam.Keyword: Capital Owners, Cooperation, Farmers